THE ESSENTIALS OF DPRD'S MAIN POINTS OF THOUGHT IN EQUITABLE REGIONAL DEVELOPMENT - Tulie, Espin; Aneta, Asna; Aneta, Yanti (Universitas Negeri Gorontalo, 2023)
This research is entitled The Essence of the Main Thoughts of the DPRD in Equitable Regional Development, with the formulation of the problem: what is the development planning process in Gorontalo Province?, what is the process for preparing the Main Thoughts (POKIR) of the DPRD?, how is the process for preparing the Regional Government Work Plan (RKPD) )?, what are the steps for synchronizing POKIR with the RKPD in Gorontalo Province?. While the research method used is a qualitative method. The Main Thoughts (POKIR) DPRD is a program of regional development activities obtained by DPRD members based on minutes of meetings, hearings, or the results of absorption of aspirations through recess, which are then entered into the Regional Government Information System (SIPD) in the form of Programs and Activities. This is done considering the existence of the DPRD as the representative of the people who are expected to accommodate and accept the various aspirations of the citizens so that their difficulties are resolved and their needs are met. Of course, the community expects the DPRD's role to continue and fight for their aspirations to receive a budget or improve facilities from the government. The topic of discussion regarding the essence of the DPRD's main thoughts in the distribution of regional development will be directed to the discussion on the active role of the DPRD in absorbing, accommodating, and fighting for the aspirations of the citizens, which are outlined in the Regional Revenue and Expenditure Budget (APBD).